ROLE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Nishonova Dildora Mashrabovna (American Journals, 2025)
This in the article artificial intellect technologies modern education in the system place and importance analysis Research during artificial intellect tools study individual approach in the process to form, knowledge evaluation automation, customized education provides and interactive teaching environment in creation efficiency Also, artificial intellect from technologies uses in the process to the surface arrival possible was social and moral problems are also covered. The article artificial intellect human factor completes not to replace, but education quality in increasing effective assistant tool as service to do emphasized.
Keywords: Artificial intellect, education technologies, customized education, automated assessment, interactive study environment, digital transformation.